A qualitative Comparative Study of the Circular Economy and the Green Pyramid Rating System for Construction and Demolition Waste Management in Algeria - Rahmouni, Thinhinane Massilia; Kalyoncuoğlu, Bahar Baser (Arab Journal for Sciences and Research Publishing, 2025)
This study provides a qualitative comparative assessment of the Circular Economy (CE) framework and the Green Pyramid Rating System (GPRS) as emerging approaches for improving construction and demolition waste (CDW) management in Algeria. The research aims to examine the advantages, limitations, and contextual applicability of both systems, and to explore their potential integration into a coherent sustainability model suited to the Algerian construction sector. A descriptive–comparative qualitative methodology was adopted, combining a systematic literature review, a case study of Algeria, and expert input collected from 21 professionals representing engineering, environmental management, and policy sectors. Data were analysed thematically and synthesised using a structured SWOT matrix. Findings show that CE offers strong potential for resource efficiency, waste minimisation, and job creation, yet remains constrained by limited recycling infrastructure and high initial investment requirements. In contrast, the GPRS provides measurable sustainability criteria at the project level and strengthens energy and resource efficiency, but suffers from low national adoption, limited professional capacity, and competition from global rating systems. Results also indicate that integrating CE’s macro-level material circularity with GPRS’s micro-level performance standards could enhance environmental outcomes and support Algeria’s transition toward sustainable construction practices. The study recommends expanding recycling infrastructure, developing regulatory incentives for green construction, localising GPRS criteria for the Algerian context, and adopting a hybrid CE–GPRS implementation roadmap to advance national CDW management strategies.